Molecular imaging of brown adipose tissue in health and disease - Bauwens, Matthias; Wierts, Roel; van Royen, Bart; Bucerius, Jan; Backes, Walter; Mottaghy, Felix; Brans, Boudewijn (European journal of nuclear medicine and molecular imaging, 2014)
Purpose Brown adipose tissue (BAT) has transformed from an interfering tissue in oncological 18 F-fluorodeoxyglucose (FDG) positron emission tomography (PET) to an independent imaging research field. This review takes the perspective from the imaging methodology on which human BAT research has come to rely on heavily. Methods This review analyses relevant PubMed-indexed publications that discuss molecular imaging methods of BAT. In addition, reported links between BAT and human diseases such as obesity are discussed, and the possibilities for imaging in these fields are highlighted. Radiopharmaceuticals aiming at several different biological mechanisms of BAT are discussed and evaluated. Results Prospective, dedicated studies allow visualization of BAT function in a high percentage of human subjects. BAT dysfunction has been implicated in obesity, linked with diabetes and associated with cachexia and atherosclerosis. Presently, 18 F-FDG PET/CT is the most useful tool for evaluating therapies aiming at BAT activity. In addition to 18 F-FDG, other radiopharmaceuticals such as 99m Tc-sestamibi, 123 I-metaiodobenzylguanidine (MIBG), 18 F-fluorodopa and 18 F-14( R , S )-[ 18 F]fluoro-6-thia-heptadecanoic acid (FTHA) may have a potential for visualizing other aspects of BAT activity. MRI methods are under continuous development and provide the prospect of functional imaging without ionizing radiation. Conclusion Molecular imaging of BAT can be used to quantitatively assess different aspects of BAT metabolic activity.